Conceptualizing Violence and Physical Violence: A Comparative Analysis of the Legislations of Peru and Chile - Fernández Ruiz, José Manuel (2022)
This research seeks to contribute to identifying the central elements of the phenomenon of violence by conceptualizing physical violence. In this way, by identifying the elements for the concept of physical violence, it also identifies the elements for a more general conception of violence and its various manifestations. While it seems intuitively obvious what constitutes physical violence, several ambiguities appear under a more detailed examination. A simple question can illustrate this: are all homicides acts of physical violence? While an intentional homicide caused by a gunshot is an act of violence, is it also a death caused in a traffic accident? There is no obvious answer to this second question. In order to develop an answer, it is necessary first to conceptualize physical violence, but there is no specific research that clarifies its meaning. The research contributes to fill this gap in the literature, identifying elements to conceptualize what physical violence is through philosophical and comparative analysis, concluding that these elements, duly modified and particularized, can be used to understand different forms of violence.